Adaptação transcultural e análise de propriedades do Evaluation of the Perception of Physical Activity (EPAP) para o português do Brasil em indivíduos com osteoartrite de joelho - Damasceno, Karen Larissa Brito (2023)
None of the available assessment instruments, cross-culturally adapted to Brazilian Portuguese, offers a specific analysis on the perception of physical activity related to individuals with knee osteoarthritis. The objective of this research was to carry out a cross-cultural adaptation of the EPPA into Brazilian Portuguese in individuals with knee OA. The sample size was set at 130 participants. Thirty of these participants were involved in obtaining the final version of the Brazilian Portuguese EPPA. The other 100 volunteers had their data used for structural and construct validity analysis. To perform the comparative analyzes, the following complementary assessment instruments were selected: Numerical Pain Scale (END), 36-item short form survey (SF-36) and Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC). The International Physical Activity Questionnaire (IPAQ) was used to classify the physical activity level of the participants. In this way, the internal consistency was continued by means of Cronbach's alpha in order to verify the presence of redundant and heterogeneous items, considering as adequate values the variation between 0.70 and 0.95. Reliability was assessed using the test-retest model using the intraclass cognitive (ICC), 95% confidence interval (CI), measurement standard error (MPE) and minimal detectable difference (DMD). Ceiling and floor effects were analyzed in the study. Most of the research participants were women, married, overweight, low level of physical activity and complete high school. The values presented in relation to reliability were excellent and substantial (values between 0.75 and 0.90). Regarding internal compliance, the values were considered adequate (values between 0.70 and 0.95). However, regarding the error, the values were considered negative (EPM=16.59%). With the aim of analyzing the construct validity, the final EPPA score was correlated with the scores of other instruments used in the study (END, WOMAC, SF-36). Of all the correlations presented, only between the EPPA and the assessment instruments: SF-36 did not present statistically significant collaboration. The Brazilian Portuguese version of the EPPA presents adequate properties regarding reliability, internal consistency and validation. No need to carry out future analyzes regarding the structure.